Low Cost Storage of Taro (Colocasia esculenta var. antiquorum) cormels - Alam, Sheriful (JOURNAL OF ROOT CROPS, 2015)
An investigation was carried out in low cost shed to establish a suitable storage method for taro cormels. Findings revealed that sprouting index increased with the advancement of storage period in all the storage methods. The lowest sprouting index was found in cormels stored in pit lined with polyethylene sheet and containing dry sand. The rotting index showed an increasing trend under the different storage methods. The rotting index and decay was lowest in cormels treated with Trichoderma viride (0.5%) and stored in pit lined with polyethylene sheet containing moist sand (5% moisture). Increasing physiological loss in weight was observed in all the storage methods with the advancement of storage period. Cormels stored in pit lined with polyethylene sheet and containing dry sand showed the least loss in physiological loss in weight, whereas the highest loss was recorded in kaccha floor (control). Starch and moisture content decreased considerably across storage. Cormels stored in pit lined with polyethylene sheet and containing dry sand retained higher values of starch and moisture throughout the storage period. Dry matter and total sugar considerably increased with advancement of storage.